Cortisol Reactivity to Social Stress as a Mediator of Early Adversity on Risk and Adaptive Outcomes. Issue 6 (6th November 2014) - Conradt, Elisabeth; Abar, Beau; Lester, Barry M.; LaGasse, Linda L.; Shankaran, Seetha; Bada, Henrietta; Bauer, Charles R.; Whitaker, Toni M.; Hammond, Jane A.
<x xml:space="preserve">Abstract</x> Children chronically exposed to stress early in life are at increased risk for maladaptive outcomes, though the physiological mechanisms driving these effects are unknown. Cortisol reactivity was tested as a mediator of the relation between prenatal substance exposure and/or early adversity on adaptive and maladaptive outcomes. Data were drawn from a prospective longitudinal study of prenatal substance exposure (N = 860). Cortisol reactivity was assessed at age 11. Among African Americans, prenatal substance exposure exerted an indirect effect through early adversity and cortisol reactivity to predict externalizing behavior, delinquency, and a positive student–teacher relationship at age 11. Decreased cortisol reactivity was related to maladaptive outcomes, and increased cortisol reactivity predicted better executive functioning and a more positive student–teacher relationship.